Jean Pillement (Lyon, 1728-1808) e os colecionadores do Porto. Pintura nos Museus Nacionais de Soares dos Reis e de Arte Antiga - Paula Mesquita Leite Santos (Midas: Museus e Estudos Interdisciplinares)
It was very difficult to document the paintings related to the foundation of Museu Nacional de Soares dos Reis and Porto city Council. However, this area proved to be a good field of research, in particular on European painting, including Jean Pillement (Lyon 1728-1808). Indeed, this French landscaper was able to work in Portugal almost without competition, responding to a certain demand from collectors. In this article, we will focus on the city of Porto, where the painter left a visible trace in paintings and drawings in private collections, ranging from the Allen Collection to the spolium of the painter Joaquim Rodrigues Braga (1793-1853), the director of Porto Academy of Fine Arts. In turn, Fr. José Mayne (1723-1792) was born in Porto but distinguished himself as a clergyman in Lisbon. He was the General of the Third Order of San Francisco and also a collector who knew Pillement, that would send him “petites bagatelles” (small mementoes). To the North of the country, the painter practiced a kind of descriptive landscape inspired on traditional river work of Douro region. At the same time the French landscaper left his influence on Domingos Francisco Vieira (1765-1805), a painter and wood gilder who lived in the Olival, next to the Clérigos Tower (Porto), father of famous Vieira Portuense. We will present some results of our research, related with the Museu Nacional de Soares dos Reis/Municipal Heritage of Porto and the Museu Nacional de Arte Antiga (Lisbon).